A research on the profile and training needs analysis of the present leaders of Chiro Pilipinas in Luzon region - Balang, Richard A. (Animo Repository, 2008)
This study endeavored to explore and assess the training needs of leaders for Chiro Movement for the region of Luzon. Interview questions were developed and administered to the present leaders of the movement. A questionnaire was distributed to the leaders last July 2008. Questions were designed to identify the common problem encountered by the leaders and their needs in terms of knowledge about Chiro, leadership, spirituality and youth ministry. Through this assessment, the researcher will be able to determine the programs which will address the results.